Effects of γ-ray treatment on paper. (April 2018) - Coppola, Floriana; Fiorillo, Flavia; Modelli, Alberto; Montanari, Matteo; Vandini, Mariangela
Abstract: The effects of γ-irradiation and thermal drying treatments at an industrial level, and accelerated ageing on the properties of pure cellulose paper are investigated with a multi-disciplinary approach. Viscometry is used for measuring the degree of polymerisation, visible reflectance spectroscopy for colour changes, tensile strength and tearing resistance tests for mechanical properties, Fourier transform IR spectroscopy and scanning electron microscopy for possible chemical or physical modifications of the surface. The results indicate that γ-rays (5 and 10 kGy) cause a sizeable reduction of the degree of polymerisation, but only small colour changes, while larger effects on the colour are caused by the synergetic effect of ageing. In spite of the large degree of polymerisation decrease, γ-irradiation is found to only slightly affect the mechanical properties, as well as thermal and ageing treatments. No clear evidence for changes in the FTIR spectral features due to the treatments employed is found. Highlights: Effects of γ-irradiation on paper are studied with a multi-disciplinary approach. Effects of additional thermal and ageing treatments are also evaluated. Irradiation causes a sizeable decrease of the degree of polymerisation. Irradiation alters only slightly mechanical and physical properties of paper. A 5 kGy dose, sufficient for effective bio-disinfection, causes acceptable damages.